Anosmia, dysgeusia and malnutrition in chronic kidney disease: A systematic review - Gaetano Ferrara; Sara Morales Palomares; Giuliano Anastasi; Mauro Parozzi; Lea Godino; Domenica Gazineo; Marco Sguanci; Stefano Mancin (Nefrología)
Chronic kidney disease (CKD) is a prevalent health condition associated with numerous complications, including olfactory and taste dysfunction, and malnutrition. This systematic review focused on dysgeusia, smell disorders and malnutrition in CKD patients. The search included scientific databases such as PubMed, Cochrane Library, CINAHL, Scopus, and Web of Science, as well as sources of grey literature. Quality assessment and risk of bias were evaluated using JBI guidelines, while the certainty of evidence was assessed with the Oxford Centre methods. Seven studies were included: two focusing on anosmia and five on dysgeusia. Anosmia was associated with poorer nutritional status, and interventions such as intranasal theophylline showed promise in enhancing olfactory function. Dysgeusia studies highlighted the potential role of zinc deficiency in malnutrition among dialysis patients, with zinc supplementation showing mixed results to improve taste dysfunction. Taste alterations were correlated with upper gastrointestinal symptoms and malnutrition in CKD patients. The analysis of the interconnection between anosmia, dysgeusia, and malnutrition emerges as a crucial starting point for improving nutritional outcomes in chronic kidney disease (CKD) patients, emphasizing the need for accurate assessment and targeted therapeutic interventions to ensure better nutritional health and improved quality of life for these patients. Resumen: La enfermedad renal crónica (ERC) es una condición de salud prevalente asociada a numerosas complicaciones, incluyendo disfunción olfativa y gustativa, así como malnutrición. Esta revisión sistemática se centró en la disgeusia, los trastornos olfativos y la malnutrición en los pacientes con ERC. La búsqueda incluyó bases de datos científicas tales como PubMed, Cochrane Library, CINAHL, Scopus y Web of Science, así como fuentes de la literatura gris. La evaluación de la calidad y el riesgo de sesgo se analizaron utilizando las guías JBI, mientras que la certidumbre de la evidencia se evaluó mediante los métodos de Oxford Centre. Se incluyeron siete estudios: dos de ellos centrados en la anosmia y cinco en la disgeusia. La anosmia estuvo asociada a un peor estatus nutricional, y las intervenciones tales como teofilina intranasal resultaron prometedoras para mejorar la función olfativa. Los estudios sobre disgeusia destacaron el rol potencial de la deficiencia de zinc en la malnutrición entre los pacientes de diálisis, y la aportación de suplementos de zinc mostró resultados mixtos para mejorar la disfunción gustativa. Las alteraciones del gusto se correlacionaron con los síntomas del tracto gastrointestinal superior y la malnutrición en los pacientes de ERC. El análisis de la interconexión entre anosmia, disgeusia y malnutrición surge como punto de inicio fundamental para mejorar los resultados nutricionales en los pacientes con ERC, subrayando la necesidad de realizar evaluaciones precisas e intervenciones terapéuticas focalizadas para garantizar una mejor salud nutricional y mejorar la calidad de vida de dichos pacientes.